Colorectal Cancer: Disease Process, Current Treatment Options, and Future Perspectives - Amusa S. Adebayo; Kafilat Agbaje; Simeon K. Adesina; Oluwabukunmi Olajubutu (MDPI AG, 2023)
Colorectal cancer (CRC) is one of the deadliest malignancies in the US, ranking fourth after lung, prostate, and breast cancers, respectively, in general populations. It continues to be a menace, and the incidence has been projected to more than double by 2035, especially in underdeveloped countries. This review seeks to provide some insights into the disease progression, currently available treatment options and their challenges, and future perspectives. Searches were conducted in the PubMed search engine in the university's online library. The keywords were "Colorectal Cancer" AND "disease process" OR "disease mechanisms" OR "Current Treatment" OR "Prospects". Selection criteria were original articles published primarily during the period of 2013 through 2023. Abstracts, books and documents, and reviews/systematic reviews were filtered out. Of over 490 thousand articles returned, only about 800 met preliminary selection criteria, 200 were reviewed in detail, but 191 met final selection criteria. Fifty-one other articles were used due to cross-referencing. Although recently considered a disease of lifestyle, CRC incidence appears to be rising in countries with low, low-medium, and medium social demographic indices. CRC can affect all parts of the colon and rectum but is more fatal with poor disease outcomes when it is right-sided. The disease progression usually takes between 7-10 years and can be asymptomatic, making early detection and diagnosis difficult. The CRC tumor microenvironment is made up of different types of cells interacting with each other to promote the growth and proliferation of the tumor cells. Significant advancement has been made in the treatment of colorectal cancer. Notable approaches include surgery, chemotherapy, radiation therapy, and cryotherapy. Chemotherapy, including 5-fluorouracil, irinotecan, oxaliplatin, and leucovorin, plays a significant role in the management of CRC that has been diagnosed at advanced stages. Two classes of monoclonal antibody therapies have been approved by the FDA for the treatment of colorectal cancer: the vascular endothelial growth factor (VEGF) inhibitor, e.g., bevacizumab (Avastin®), and the epidermal growth factor receptor (EGFR) inhibitor, e.g., cetuximab (Erbitux®) and panitumumab (Verbitix®). However, many significant problems are still being experienced with these treatments, mainly off-target effects, toxic side effects, and the associated therapeutic failures of small molecular drugs and the rapid loss of efficacy of mAb therapies. Other novel delivery strategies continue to be investigated, including ligand-based targeting of CRC cells.